“A Face Calmly Looking into the Darkness”: An Understanding of the Essence of Poetry in the Later Poems of Dan Pagis (Филологический класс, 2022)
In a number of later poems, the Israeli poet Dan Pagis (1930–1986) persistently reproduced one and the same plot: the fullness of expression achieved by the artist suddenly turns into emptiness, and the seemingly unrestricted possibility of free poetic speech turns into silence. It seems, this paradox is due to the denial of the principle of mimesis (when art is interpreted as the practice of a continuously renewed, but obviously unattainable representation) and the poet’s attraction to such a statement, which ideally could become a form of silence. For example, in the prose miniature “Towards a literary survey” it is said that poems are written with “sympathetic ink”, and the poem “Small Poetics” depicts the process of creating a poetic text as passive listening to the “voice of a blank sheet”. The purpose of this article is to reconstruct the understanding of the essence of poetry, underlying these and some other (rather numerous) texts of Pagis, which can be conditionally called “poems about art”. The analysis carried out takes into account, among other things, the circumstances of the biographical plan – mainly, memories of the events experienced by the poet during the period of the Jewish Holocaust. The internally incomplete experience of being in his own past, perceived as a continuous but invariably unsuccessful return from the world of the dead to the world of the living, prompts the lyrical protagonist of Pagis (the poet) to perceive the writing of poetry as a painful attempt to overcome the horror of the emptiness surrounding him. At the same time, the poetic text turns out to be nothing more than a system of “scaffolding” (definition by the Israeli literary critic Vered Karti Shem Tov), which is not intended to erect a new building (“house” as an image of the world order), but only so that in this emptiness it might find at least some – albeit very fragile – support.